Surgical Treatment of Muscular Sports Injuries - Takesita, Mituru; Hirata, Osamu; Ogami, Toshihiro; Iwamoto, Hideaki; Aramaki, Kenichi (Orthopedics & Traumatology, 1995)
Sporting injuries commonly cause strain and/or contusion of muscles, the treatment of which is generally RICE (Rest, Ice, Compression and Elevation) acute stage and an early sporting rehabilitation program. Surgery for such injuries is rarely indicated. In our hospital, surgical treatment (removal of hematoma and suture of torn muscles) was performed in 3 out of 54 cases with sporting injuries within a one yearperiod. These 3 cases had severe symptoms (gait disturbance and intractable motion pain) and large intramuscular hematoma shown on MRI. All three cases had a complete recovery postoperatively, allowing the to return to full sporting activities.